Epoxidized soybean oil-lignin-polyacid ternary adhesive and preparation method thereof

By combining epoxy soybean oil, lignin and polyacid and undergoing mechanical and chemical treatment, epoxy soybean oil-lignin-polyacid ternary adhesive with high adhesive properties is prepared, which solves the shortcomings of bio-based adhesives in terms of bonding strength, water resistance and heat resistance, and achieves higher industrial application performance and environmental protection performance.

CN118085816BActive Publication Date: 2025-04-01FUJIAN AGRI & FORESTRY UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410265557.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-08
Publication Date
2025-04-01
Estimated Expiration
2044-03-08

AI Technical Summary

Technical Problem

The existing bio-based adhesives are difficult to compare with traditional petroleum-based adhesives in terms of bonding strength, water resistance and heat resistance, especially in high humidity or high temperature environments, which limits their application in outdoor furniture and building materials.

Method used

Using ternary combinations of epoxy soybean oil, lignin and polyacid, lignin is processed through mechanical grinding and chemical treatment, and compounded with epoxy compounds, ternary adhesives with high adhesion properties are prepared.

Benefits of technology

It improves the adhesive strength, water resistance and heat resistance, solves the limitations of traditional bio-based adhesives in these aspects, and simplifies the production process, reduces costs, and is suitable for industrial-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses an epoxy soybean oil-lignin-polyacid ternary adhesive and a preparation method and application thereof, wherein lignin, polyol and water are mixed and then mechanically ground, and then the ground product is mixed, stirred or ground with epoxy soybean oil, polyacid / anhydride and solvent to obtain the ternary adhesive. The present invention makes full use of the natural advantages of lignin and epoxy soybean oil, improves the overall performance of the adhesive through a simplified preparation method, solves the problem that traditional petroleum-based adhesives release harmful substances, and the performance stability of bio-based adhesives is limited under high humidity or high temperature environments. The adhesive can be widely used in the fields of plywood, fiberboard, particleboard, bamboo-wood composite board, etc., and has excellent environmental performance and industrial application performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of adhesives, and in particular relates to an epoxy soybean oil-lignin-polyacid ternary adhesive and a preparation method and application thereof. Background Art

[0002] Traditional adhesives, such as petroleum-based phenolic resins and urea-formaldehyde resins, are widely used due to their good bonding properties and low cost. However, these adhesives release harmful substances, such as formaldehyde, during production and use, which pose a major threat to the environment and human health. In addition to the negative impact on the environment, these products rely on non-renewable resources. With the increasing global attention to environmental protection and sustainable development, adhesives are under pressure to transform.

[0003] In the existing market, the demand for efficient and environmentally friendly adhesives has increased dramatically, especially in the manufacture of plywood, fiberboard, particleboard and bamboo-wood composite materials. However, existing bio-based adhesive products often find it difficult to find a balance between environmental performance and industrial application performance. The market urgently needs an adhesive that can meet environmental protection standards and provide excellent bonding performance.

[0004] In recent years, epoxy soybean oil-based adhesives have attracted widespread attention as an alternative due to the use of renewable soybean oil as a raw material. However, despite the significant advantages of these adhesives in terms of environmental friendliness, in practical applications, these adhesives are often not comparable to traditional petroleum-based adhesives in terms of key properties such as bonding strength, water resistance and heat resistance. In particular, performance stability issues in high humidity or high temperature environments limit their application in areas such as outdoor furniture and building materials.

[0005] Lignin is a natural polymer material with a wide range of sources, one of which is the by-product of the pulp and paper industry. In its natural state, lignin is a rigid three-dimensional network rich in phenolic structures and has a variety of functional groups, such as hydroxyl groups (-OH), which can form bonds and cross-links with the substrate to produce a solid matrix, thereby producing an adhesive effect. However, the current market share of lignin adhesives is very small, mainly because the chemical composition and structural characteristics of lignin make it difficult to achieve ideal bonding effects in traditional adhesive formulations.

[0006] In view of this, the present invention proposes an epoxy soybean oil-lignin-polyacid ternary adhesive and its preparation method and application. The present invention makes full use of the natural advantages of lignin resources, optimizes the overall performance of the adhesive by compounding it with epoxy compounds, and solves the limitations of traditional bio-based adhesives in terms of bonding strength, water resistance and heat resistance. At the same time, the preparation method of the present invention simplifies the production process and reduces costs, making it more feasible in industrial-scale production. Summary of the invention

[0007] In order to solve the deficiencies of the prior art, the present invention provides an epoxy soybean oil-lignin-polyacid ternary adhesive and a preparation method and application thereof.

[0008] To achieve the above object, the present invention adopts the following technical solution:

[0009] A method for preparing an epoxy soybean oil-lignin-polyacid ternary adhesive comprises the following steps:

[0010] (1) mixing lignin, polyol and water and then mechanically grinding them;

[0011] (2) The ground product obtained in step (1) is treated according to any of the following steps:

[0012] a) after the grinding in step (1) is completed, adding epoxidized soybean oil, polyacid / anhydride and solvent and continuing grinding to obtain the ternary adhesive;

[0013] b) mixing the ground product of step (1) with epoxidized soybean oil, polyacid / anhydride and solvent, and reacting by stirring to obtain the ternary adhesive.

[0014] Furthermore, the lignin in step (1) includes one or more of lignin residues from the papermaking industry and kraft lignin, alkali lignin, enzymatic lignin, straw lignin, softwood lignin, hardwood lignin, and organic lignin.

[0015] Furthermore, the polyol in step (1) is one or more of ethylene glycol, propylene glycol, glycerol, polyethylene glycol, polypropylene glycol, polyglycerol, and pentaerythritol.

[0016] Furthermore, the amount of polyol added in step (1) is 1%-100% of the mass of the lignin, preferably 5%-80%, more preferably 10%-50%, and most preferably 10%-30%.

[0017] Furthermore, the amount of water added in step (1) is 10%-300% of the mass of the lignin, preferably 50%-200%, more preferably 50%-100%, and most preferably 50%-70%. In actual use, the amount of water added should be adjusted according to the type of lignin and the mass of the added polyol to ensure that the powder can be completely wetted.

[0018] Furthermore, the temperature of the mechanical grinding in step (1) is 30-100° C. The grinding time depends on the grinding process adopted, and is generally 5-180 min, preferably 10-150 min, more preferably 10-60 min, and most preferably 10-20 min.

[0019] Furthermore, the particle size of the grinding product in step (1) is below 1200 nm, preferably below 1000 nm, and more preferably below 800 nm.

[0020] Furthermore, the amount of epoxidized soybean oil added in step (2) is 0.01%-100% of the mass of the ground product, preferably 5%-100%, more preferably 10%-100%, more preferably 10%-80%, most preferably 20%-60%.

[0021] Furthermore, the polyacid in step (2) is one or more of oxalic acid, citric acid, malic acid, lactic acid, tartaric acid, maleic acid, fumaric acid, and phthalic acid; and the acid anhydride is one or more of maleic anhydride, bismaleic anhydride, and pyromellitic anhydride.

[0022] Furthermore, in step (2), the amount of the polyacid / anhydride added is 1%-100% of the mass of the ground product, preferably 10%-100%, more preferably 20%-100%, and most preferably 30%-100%.

[0023] Furthermore, the solvent in step (2) is one or more of water, 1,4-dioxane, 4-methylbutyrolactone, 2-methyltetrahydrofuran, methanol, ethanol, propanol, butanol, acetone and butanone.

[0024] Furthermore, the amount of solvent added in step (2) is 0%-300% of the mass of the ground product, preferably 0%-100%, more preferably 0-50%, and most preferably 0-20%.

[0025] Furthermore, the grinding time in step a) is 1-20 min, preferably 1-10 min, and more preferably 5-10 min.

[0026] Furthermore, in step b), the stirring reaction is carried out at a temperature of 30-180°C, preferably 50-180°C, more preferably 70-180°C, more preferably 70-150°C, most preferably 70-120°C, and for 5-60 min.

[0027] The epoxy soybean oil-lignin-polyacid ternary adhesive prepared by the above method can be used to bond raw wood boards, artificial boards, particle boards, metals or plastics.

[0028] Furthermore, in the bonding of log boards, artificial boards or particle boards, the adhesive is directly applied to the surface of log boards, artificial boards or particle boards, and cross-linked by hot pressing to achieve the bonding effect on the wood. During the hot pressing process, the added polyols and polyacids / anhydrides react with lignin to form ester bonds or ether bonds, thereby strengthening the bonding effect, so there is no need to remove them. The bio-based adhesive can be directly used in the field of curing and bonding by hot pressing without further reaction or addition of other active ingredients. In practical applications, the hot pressing temperature can be adjusted according to actual needs (such as board thickness, moisture, etc.). The temperature of the hot pressing cross-linking is 100-220°C, preferably 110-200°C, more preferably 120-200°C, and most preferably 150-190°C. The pressure of the hot pressing cross-linking is 0.4-3Mpa, preferably 0.5-2.5Mpa, and more preferably 0.7-2.0Mpa.

[0029] Furthermore, in the bonding of metal or plastic, the adhesive is directly applied to the metal or plastic surface, and then dried in an oven at 100-200°C for 1-12 hours to bond the metal or plastic. For metal, the drying temperature is 100-200°C, more preferably 150-200°C, and most preferably 180-200°C. For plastic, the drying temperature depends on the melting point of the plastic. When it is lower than the melting point of the plastic, the drying temperature is preferably above 100°C.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The present invention proposes a method for preparing an epoxy soybean oil-lignin-polyacid ternary adhesive, which mechanically and chemically treats lignin and compounds it with an epoxy compound to obtain an epoxy soybean oil-lignin-polyacid ternary adhesive with high adhesion. This method simplifies the synthesis process of traditional adhesives and reduces the use of harmful chemicals. Unlike the existing patents that extract lignin from wood powder through multiple steps to make adhesives, which requires a large amount of solvents, modifiers and multiple steps of separation and purification operations, the present invention improves its reactivity and dispersibility through micro-nano processing, which helps to improve the viscosity, viscosity and thermodynamic stability of the adhesive and reduce waste generation and emissions.

[0032] (2) The amount of dispersant, modifier and solvent used in the present invention is relatively small. Unlike the existing patents that use chemical methods to modify lignin to prevent the self-polymerization of degraded lignin units under acidic conditions, which requires the use of modifiers and solvents such as formaldehyde, polyoxymethylene, and acetone, the present invention innovatively uses a mechanochemical method to nano-micronize biomass particles, fully expose the active groups of lignin, greatly increase its specific surface area, and effectively enhance the reaction activity. The process is simple, reducing the complexity and operating costs of producing lignin-based adhesives, effectively improving the process economy, and being more suitable for large-scale applications. It is a more green and sustainable process.

[0033] (3) The lignin grinding product obtained in the present invention has good physical and chemical stability and is easy to store and transport. Step (1) and step (2) can be carried out separately and then compounded with a modifier before use, which can effectively prevent denaturation and inactivation, and also avoid the use of other stabilizers.

[0034] (4) The present invention completely avoids the use of aldehyde chemicals. The small amount of additives used in the process can be selected from environmentally friendly and non-toxic chemicals, achieving the requirements of no aldehyde in the whole process, environmental friendliness and green chemistry.

[0035] (5) The ternary adhesive produced by the present invention has high bonding strength, which solves the problem of poor water resistance of current bio-based adhesives. DETAILED DESCRIPTION

[0036] A method for preparing an epoxy soybean oil-lignin-polyacid ternary adhesive comprises the following steps:

[0037] (1) Mix lignin with 1%-100% of its mass of polyol and 10%-300% of water, and grind mechanically at 30-100°C until the particle size is below 1200nm;

[0038] (2) The ground product obtained in step (1) is treated according to any of the following steps:

[0039] a) after the grinding in step (1) is completed, adding epoxidized soybean oil, polyacid / anhydride and solvent and continuing grinding for 1-20 minutes to obtain the ternary adhesive;

[0040] b) mixing the ground product of step (1) with epoxidized soybean oil, polyacid / anhydride and solvent, and reacting by stirring at 30-180° C. to obtain the ternary adhesive.

[0041] Wherein, the lignin in step (1) includes one or more of lignin residues from the papermaking industry and kraft lignin, alkali lignin, enzymatic lignin, straw lignin, softwood lignin, hardwood lignin, and organic lignin. The polyol is one or more of ethylene glycol, propylene glycol, glycerol, polyethylene glycol, polypropylene glycol, polyglycerol, and pentaerythritol.

[0042] In step (2), the amount of epoxidized soybean oil added is 0.01%-100% of the mass of the ground product, the amount of polyacid / anhydride added is 1%-100% of the mass of the ground product, and the amount of solvent added is 0%-300% of the mass of the ground product.

[0043] The polyacid is one or more of oxalic acid, citric acid, malic acid, lactic acid, tartaric acid, maleic acid, fumaric acid, and phthalic acid; the acid anhydride is one or more of maleic anhydride, bismaleic anhydride, and pyromellitic dianhydride. The solvent is one or more of water, 1,4-dioxane, 4-methylbutyrolactone, 2-methyltetrahydrofuran, methanol, ethanol, propanol, butanol, acetone, and butanone.

[0044] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0045] Example 1

[0046] (1) Mix 100 g of alkali lignin raw material (water content 20%), 40 g of ethylene glycol and 150 g of water, add to a colloid mill and grind at room temperature for 20 min;

[0047] (2) 100 g of the ground product obtained in step (1), 50 g of epoxidized soybean oil and 50 g of citric acid were mixed and stirred at 70°C for 10 min to prepare an adhesive.

[0048] Example 2

[0049] The 40 g of ethylene glycol in step (1) was replaced with 20 g of ethylene glycol, and the other steps were the same as in Example 1.

[0050] Example 3

[0051] The 40 g of ethylene glycol in step (1) was replaced with 60 g of ethylene glycol, and the other steps were the same as those in Example 1.

[0052] Example 4

[0053] The 40 g of ethylene glycol in step (1) was replaced with 40 g of polyethylene glycol (molecular weight 2000). The other steps were the same as in Example 1.

[0054] Example 5

[0055] The 20 min colloid mill treatment in step (1) was replaced with a high-pressure homogenizer for 7 cycles, and the other steps were the same as in Example 1.

[0056] Example 6

[0057] The colloid mill treatment for 20 min in step (1) was replaced with a colloid mill treatment for 10 min, and the other steps were the same as in Example 1.

[0058] Example 7

[0059] The colloid mill treatment for 20 min in step (1) was replaced with a colloid mill treatment for 30 min, and the other steps were the same as in Example 1.

[0060] Example 8

[0061] The 50 g of citric acid in step (2) was replaced with 30 g of citric acid, and the other steps were the same as those in Example 1.

[0062] Example 9

[0063] The 50 g of citric acid in step (2) was replaced with 70 g of citric acid, and the other steps were the same as those in Example 1.

[0064] Example 10

[0065] The 50 g of citric acid in step (2) was replaced by 50 g of phthalic acid, and the other steps were the same as those in Example 1.

[0066] Embodiment 11

[0067] The 50 g of citric acid in step (2) was replaced by 50 g of maleic anhydride, and the other steps were the same as those in Example 1.

[0068] Example 12

[0069] The 50 g of epoxidized soybean oil in step (2) was replaced with 30 g of epoxidized soybean oil. The other steps were the same as those in Example 1.

[0070] Example 13

[0071] The 50 g of epoxidized soybean oil in step (2) was replaced with 70 g of epoxidized soybean oil. The other steps were the same as those in Example 1.

[0072] Embodiment 14

[0073] The 100 g of alkaline lignin in step (1) was replaced with 100 g of enzymatic lignin (water content 15%), and the other steps were the same as in Example 1.

[0074] Embodiment 15

[0075] The 100 g alkali lignin in step (1) was replaced with 100 g sulfonate lignin (water content 15%). The other steps were the same as in Example 1.

[0076] Example 16

[0077] The 150 g of water in step (1) was replaced with 100 g of water, and the other steps were the same as in Example 1.

[0078] Embodiment 17

[0079] The 150 g of water in step (1) was replaced with 200 g of water, and the other steps were the same as in Example 1.

[0080] Embodiment 18

[0081] In step (2), 20 g of methanol was added, and the other steps were the same as those in Example 1.

[0082] Comparative Example 1

[0083] The 40 g of ethylene glycol in step (1) was replaced with 40 g of water, and the other steps were the same as in Example 1.

[0084] Comparative Example 2

[0085] The 20 min colloid mill treatment in step (1) was replaced by 20 min stirring, and the other steps were the same as in Example 1.

[0086] Comparative Example 3

[0087] The 50 g citric acid in step (2) was replaced by 50 g phosphoric acid, and the other steps were the same as those in Example 1.

[0088] Application experiment example:

[0089] 1. Performance test of three-layer plywood prepared with adhesive

[0090] The epoxy soybean oil-lignin-polyacid ternary adhesive prepared in the examples and comparative examples was made into plywood according to the following method and tested.

[0091] The plywood manufacturing and strength testing are carried out in accordance with Section 4.17 of GB / T17657-2022 "Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels". The specific preparation steps are as follows:

[0092] (1) Select fast-growing poplar veneers to prepare three-layer plywood. The moisture content of the veneers is 10%-12%. The length, width and thickness of the veneers are 145 mm, 110 mm and 1.5 mm respectively. The prepared adhesive is used to glue the middle veneer. The gluing method is double-sided gluing, and the single-sided gluing amount is 100 g / m 2 .

[0093] (2) Glue an un-glued veneer to the upper and lower sides of the glued veneer so that the fiber directions of adjacent veneers are perpendicular to each other. Place the assembled three-layer plywood on the heating plate of the hot press. The hot pressing temperature is 180°C, the hot pressing pressure is 2 MPa, and the hot pressing time is 5 min.

[0094] The obtained plywood was tested according to the standard GB / T 9846-2015 “Ordinary Plywood”, and the results are shown in Table 1.

[0095] Table 1 Bonding strength of epoxy soybean oil-lignin-polyacid ternary adhesive

[0096]

[0097] It can be seen from Table 1 that the ternary adhesive prepared in the embodiment has good cross-linking performance, and the strength of the three types of boards is greater than the national standard 0.7 MPa; the adhesive without mechanical grinding or compounding with solvent / modifier cannot provide the required adhesive strength.

[0098] It can be seen from Examples 1-4 and Comparative Example 1 that the addition of polyols is very important for the bonding performance of the epoxy soybean oil-lignin-polyacid ternary adhesive, and cross-linking performance cannot be produced without the action of polyols. Ethylene glycol is an excellent dispersant that can effectively improve the bonding performance of the adhesive, because the penetration of ethylene glycol into lignocellulosic biomass can cause chemical changes, such as lignin delignification, lignin structure changes, and the formation of solvent-biomass composites.

[0099] It can be seen from Examples 5-7 and Comparative Example 2 that the lignin treated with a colloid mill or a high-pressure homogenizer has better cross-linking properties. This may be because the colloid mill or the high-pressure homogenizer treatment can achieve nano-micronization of the powder (after testing, the average particle size of the products after grinding in Examples 5-7 and Comparative Example 2 was 121 nm, 351 nm, 194 nm and 13500 nm, respectively), which increases the specific surface area of ​​the particles and exposes more active sites.

[0100] It can be seen from Examples 8-11 and Comparative Example 3 that the addition of polyacids / acid anhydrides is also necessary to improve the performance of viscose. The addition of polyacids / acid anhydrides is conducive to the formation of a cross-linked network of nanocellulose lignin particles, thereby improving the bonding strength.

[0101] Examples 12-13 can prove that epoxidized soybean oil can help form a cross-linked network, thereby improving the bonding strength. Examples 14-15 can prove that this method can provide excellent cross-linking properties for adhesives prepared from lignin from various sources. Examples 16-17 illustrate that appropriate water content in the system can help improve the bonding properties of the resulting adhesive. Example 18 illustrates that adding a small amount of methanol can help form a cross-linked network and improve the bonding strength.

[0102] The above plywood strength experiment proves that the adhesive produced by the preparation method of the epoxy soybean oil-lignin-polyacid ternary adhesive provided by the present invention has good adhesive properties and can achieve a bonding strength far greater than the national standard of 0.7 MPa.

[0103] (II) Performance test of adhesive bonding smooth low-carbon steel plate

[0104] The adhesives obtained in Examples 1, 10 and 11 are used to bond low carbon steel sheets, and the specific operation process is as follows:

[0105] (1) Polishing of low carbon steel sheet: Take a steel sheet of size 12 mm × 89 mm, first polish it with a black diamond stick, then polish it with a regular green diamond stick, wipe off the excess grease, and then clean it with a solvent composed of equal volumes of n-hexane, acetone, MeOH and deionized water. Let it dry overnight before use;

[0106] (2) The adhesive obtained in the example is evenly applied to the treated steel sheet surface, with an application amount of 100 g / m 2 ;

[0107] (3) Overlap and press the two steel sheets coated with adhesive, put them in an oven and dry them at 180°C for 24 hours, then cool them naturally to room temperature;

[0108] (4) The tensile strength was tested using an MTS Insight materials testing instrument equipped with a 10 kN load cell.

[0109] The experimental results show that the tensile strength of steel plates bonded with the adhesives of Examples 1, 10 and 11 are 14.3 MPa, 10.2 MPa and 11. MPa respectively, which indicates that the type of polyacid / anhydride will affect the bonding performance of the adhesive. Citric acid can significantly improve the strength of the adhesive because it can produce ester bonds with lignin and epoxy soybean oil.

[0110] The description and explanation of the above embodiments can enable those skilled in the art to understand and implement the present invention. However, the present invention will not be limited to the above embodiments. The inventive principles disclosed herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Modifications to these embodiments should be obvious to those skilled in the art and will still be within the scope of protection of this patent.

Claims

1. A method for preparing an epoxy soybean oil-lignin-polyacid ternary adhesive, characterized in that: The steps include: (1) mixing lignin, polyol and water and then mechanically grinding them; (2) The ground product obtained in step (1) is treated according to any of the following steps: a) after the grinding in step (1) is completed, adding epoxidized soybean oil, polyacid / anhydride and solvent and continuing grinding to obtain the ternary adhesive; b) mixing the ground product of step (1) with epoxidized soybean oil, polyacid / anhydride and solvent, and reacting by stirring to obtain the ternary adhesive; In step (1), the amount of polyol added is 1%-100% of the weight of the lignin, and the amount of water added is 10%-300% of the weight of the lignin; In step (2), the amount of epoxidized soybean oil added is 10%-100% of the mass of the ground product, the amount of polyacid / anhydride added is 10%-100% of the mass of the ground product, and the amount of solvent added is 0%-300% of the mass of the ground product.

2. The method for preparing the epoxy soybean oil-lignin-polyacid ternary adhesive according to claim 1, characterized in that: The lignin in step (1) includes lignin residues from the papermaking industry and one or more of kraft lignin, alkali lignin, enzymatic lignin, straw lignin, softwood lignin, hardwood lignin, and organic lignin; the polyol is one or more of ethylene glycol, propylene glycol, glycerol, polyethylene glycol, polypropylene glycol, polyglycerol, and pentaerythritol.

3. The method for preparing the epoxy soybean oil-lignin-polyacid ternary adhesive according to claim 1, characterized in that: The temperature of the mechanical grinding in step (1) is 30-100° C.; the particle size of the grinding product is below 1200 nm.

4. The method for preparing the epoxy soybean oil-lignin-polyacid ternary adhesive according to claim 1, characterized in that: The polyacid in step (2) is one or more of oxalic acid, citric acid, malic acid, lactic acid, tartaric acid, maleic acid, fumaric acid, and phthalic acid; the acid anhydride is one or more of maleic anhydride, bismaleic anhydride, and pyromellitic dianhydride; and the solvent is one or more of water, 1,4-dioxane, 4-methylbutyrolactone, 2-methyltetrahydrofuran, methanol, ethanol, propanol, butanol, acetone, and butanone.

5. The method for preparing the epoxy soybean oil-lignin-polyacid ternary adhesive according to claim 1, characterized in that: The grinding time in step a) is 1-20 min.

6. The method for preparing the epoxy soybean oil-lignin-polyacid ternary adhesive according to claim 1, characterized in that: Step b) The stirring reaction temperature is 30-180°C.

7. An application of the epoxy soybean oil-lignin-polyacid ternary adhesive prepared by the method of claim 1 in wood bonding, characterized in that: The adhesive is directly applied to the surface of the original wood board, artificial board or particle board, and hot-pressed and cross-linked at 100-220°C to achieve the bonding effect on the wood.

Citation Information

Patent Citations

  • Raw materials and methods of manufacturing bio-based epoxy resins

    US20140235811A1

  • Bio-polyol composition and bio-polyurethane foam material

    US20150183948A1

  • Process for the production of epoxy resins

    US20220002473A1